Effect of Leadership Development on Employee Performance a Case of Selected Banking Sector in Pakistan - Sarwar, M. Basim (2014)
This research study is aimed at exploring, testing and establishing the relationship between leadership development and employee performance in the banking sector of Pakistan. Leadership is a well-recognized term and concept in Human resource in particular and business studies in general, however very less attention has been given to the idea and its possibilities in Pakistan. This research has been conducted to establish whether there is a relationship between leadership development and the performance of employees. Five factors of leadership development; coaching, training and development, empowerment, participation and authorization were considered. A sample size of 200 employees of the banks of Pakistan was taken. The results revealed that leadership development is positively and significantly correlated to employee performance.